Parathyroid hormone pulsatility： physiological and clinical aspects - Chiavistelli, Silvia; Giustina, Andrea; Mazziotti, Gherardo (Bone Research, 2015)
Parathyroid hormone （PTH） secretion is characterized by an ultradian rhythm with tonic and pulsatile components. In healthy subjects, the majority of PTH is secreted in tonic fashion, whereas approximately 30% is secreted in low-amplitude and high-frequency bursts occurring every 10-20 min, superimposed on tonic secretion. Changes in the ultradian PTH secretion were shown to occur in patients with primary and secondary osteoporosis, with skeletal effects depending on the reciprocal modifications of pulsatile and tonic components. Indeed, pathophysiology of spontaneous PTH secretion remains an area potentially suitable to be explored, particularly in those conditions such as secondary forms of osteoporosis, in which conventional biochemical and densitometric parameters may not always give reliable diagnostic and therapeutic indications. This review will highlight the literature data supporting the hypothesis that changes of ultradian PTH secretion may be correlated with skeletal fragility in primary and secondary osteoporosis.